2009
DOI: 10.1039/b904382a
|View full text |Cite
|
Sign up to set email alerts
|

Duplicating “sunlight” from simple WOLEDs for lighting applications

Abstract: Simple single-dopant white organic light-emitting devices (WOLEDs) with optimized efficiency/color quality/brightness trade-offs are developed; the white light produced shows the best color quality ever exhibited by WOLEDs at very high brightness, and is even able to duplicate the natural sunlight source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 138 publications
(57 citation statements)
references
References 34 publications
1
56
0
Order By: Relevance
“…The corresponding CIE coordinates are (0.42, 0.38) [45]. The highest CRI based on the monomer excimer approach was reported by Zhou et al using Pt-Ge doped into CBP host material [46]. At the emitter concentration of 10 wt% for Pt-Ge, the CIE coordinates of (0.354, 0.360) were obtained with a very high CRI of 97.…”
Section: Fluorescence and Phosphorescencementioning
confidence: 88%
“…The corresponding CIE coordinates are (0.42, 0.38) [45]. The highest CRI based on the monomer excimer approach was reported by Zhou et al using Pt-Ge doped into CBP host material [46]. At the emitter concentration of 10 wt% for Pt-Ge, the CIE coordinates of (0.354, 0.360) were obtained with a very high CRI of 97.…”
Section: Fluorescence and Phosphorescencementioning
confidence: 88%
“…Numerous studies have been reported in obtaining high CRI, which include the use of multiple emissive layers, 3 three different emitters in one single emissive layer, combining blue fluorescent dye with green and red phosphors to obtain high CRI with a near 100% internal quantum efficiency (IQE) 4 and exciplex emission. 5,6 However, the resulting efficiency is not sufficiently high for illumination at high brightness. Several approaches are therefore employed herein in order to probe the possibility of fabricating an OLED with a highest CRI while still having a relatively high power efficiency.…”
Section: Methodsmentioning
confidence: 99%
“…A mixture of impy (4) (6.0 g, 22.5 mmol), iridium(III) chloride hydrate (3.2 g, 10.7 mmol), 2-ethoxyethanol (60 mL), and water (20 mL) was deoxygenated and then heated to reflux under nitrogen for 24 h at 120 C. After cooling to room temperature, the mixture was filtrated and washed with ethanol to give product Ir(III)-m-chloride-bridged dimer (5). A mixture of the Ir(III)-mchloride-bridged dimer (5.80 g, 5.88 mmol), 2,2,6,6-tetramethyl-3,5-heptanedione (3.68 mL, 17.6 mmol), K 2 CO 3 (5.70 g, 41.24 mmol), and ethoxyethanol (40 mL) was deoxygenated and heated to reflux under nitrogen for 24 h at 120 C. After cooling to room temperature, the mixture was evaporated under vacuum and extracted with dichloromethane (100 mL).…”
Section: Synthesis Of (Impy) 2 Ir(tmd) (6)mentioning
confidence: 99%